Hubungan Karakteristik Demografis (Usia dan Jenis Kelamin) dan Kualitas Tidur dengan Risiko Terjadinya Gerd pada Masyarakat Perkotaan Rt 001/Rw 016 dan Rt 06/Rw 006 Kelurahan Cililitan, Jakarta Timur dan Tinjauannya Menurut Pandangan Islam - Shaffdika, Kyra Narumi Najwa; Eliana, Fatimah; Arsyad, Muhammad (Syntax Corporation, 2026)
Gastro-esophageal reflux disease (GERD) is a digestive disorder characterized by the backflow of stomach acid into the esophagus, causing symptoms such as heartburn and acid regurgitation. The prevalence of GERD shows a significant upward trend. In Indonesia, the prevalence of GERD in urban populations is reported to reach 9,35%. Demographic characteristics, such as age and gender, are known to influence GERD risk. In addition, poor sleep quality, which is common in urban communities, is thought to contribute to GERD incidence. This study employed a quantitative cross-sectional design using primary data. Data were collected through questionnaires assessing respondents’ demographic characteristics, sleep quality, and GERD. Data analysis was conducted using the chi-square test to determine the relationships between variables. Sleep quality was the only variable significantly associated with the risk of GERD (p = 0,004). In contrast, age (p = 0,451) and gender (p = 0,627) showed no significant association. Poor sleep quality may increase esophageal sensitivity to gastric acid, thereby increasing the risk of GERD. This study shows a significant relationship between sleep quality and the risk of GERD in the urban communities of RT 001/RW 016 and RT 006/RW 006, Cililitan Subdistrict, East Jakarta. Meanwhile, age and gender do not have a significant association. From an Islamic perspective, maintaining health is the responsibility of every individual regardless of age or gender, which can be achieved through the implementation of regular eating and sleeping patterns as a preventive measure to reduce the incidence of GERD.